Conflict in the global workplace - Stohl, Cynthia; McCann, Robert M.; Abu Bakar, Hassan (SAGE Publications, Inc., 2013)
Conflict in the global workplace Globalization and the increased complexity and interdependence of contemporary issues have concomitantly created a greater need for organizational cooperation and a greater possibility for organizational conflict.Contemporary issues such as the global distribution of goods and the need for healthy work environments are so complex they require cooperation and new forms of partnerships among organizations from different sectors of society and cultural groups.Digitized technology and mobile media also enable participation of different cultural and organizational actors who had heretofore been denied access to organizational problem-solving arenas.In this chapter, we explore the dynamic relationship between global diversity and organizational conflict.Diversity is not just something we strive for in contemporary organizations, it is a fact of life in all the joint ventures that are at the core of the globalized workplace.But it is not just the large global issues and joint collaborations that ...